SOURCES AND HISTORIOGRAPHY OF DISCREDITOLOGY AS WORLDWIDE VALUE OF JUDGE IN CRIMINAL PROCEEDINGS - OSTAFIICHUK, LIUDMYLA (Ehrlich's Journal, 2023)
The article is devoted to the establishment of judicial discretion and historiography of the research concerning this phenomenon in criminal proceedings. Found, that discretion in general, as a comprehensive, integrated legal phenomenon experienced the same milestones of evolution of legal thought, that thinking in general. This process was influenced by neolithic legal thinking, natural and sociological jurisprudence and other trends in the ontology of law. The discretionary powers of the judge are considered through his worldview values which must be organically embedded in public values. After all, the existing positive legal norms do not always flexibly respond to the challenges of society. And the legislator is not in a position to predict and reflect in detail all possible ways of resolving disputed issues in the law. Therefore, it is limited to the establishment of general rules that on the one hand, enable the judge to take into account the individual characteristics of both the offender, the offended, and on the other side, exclude judicial arbitrariness. If legislators reduces evaluation concept of the right to a minimum – the right turns into a brutal punitive mechanism. The example of Soviet law proved that the lack of judicial discretion turned the Soviet court ordered to form sentences. For the same reason, judge discretion wasn’t studied in Soviet jurisprudence and the present ones were under the ideologies pressure of that time. At the present stage of scientific development, the right to discretion in deciding criminal cases is seen as an important component of the powers of the court. Therefore a judge must be a highly moral person and be able to make decisions on his own terms according to the laws of religion and nature, to rely on the common sense and interests of the state. The ability of a judge to listen to his own heart at the time of making a judgment sees the effect of natural law – the right to justice.